2016
DOI: 10.1002/pd.4754
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on first trimester three‐dimensional placental volumetry predicting small for gestational age infants

Abstract: The mean PV estimation of the studies analyzed was burdened by a high degree of heterogeneity. Instead, discordant results were reported for the possible prediction of SGA infants using PV. Surprisingly, just two articles reported the DR for SGA infants and also had proper statistical power. The discriminatory ability of using PV alone for predicting SGA appears to be modest, but could successfully be integrated into a multivariable screening method for SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
1
20
0
3
Order By: Relevance
“…In particular, higher first trimester maternal nutritional scores were associated with increased PAPP-A concentrations, lower UtA mean PI, and decreased placental volumes at the first trimester screening ultrasound, whereas no associations were detected with free β-HCG. The obtained measurements of placental volume were comparable with previous data and small variations could be firstly dependent on the mean gestational age at the ultrasound scan, as the placenta more than doubles its volume starting from 11 to 14 weeks [ 14 , 15 ]. The analysis on birth outcomes additionally showed a positive association between the maternal nutritional score and gestational age at birth ( p = 0.05).…”
Section: Discussionsupporting
confidence: 83%
“…In particular, higher first trimester maternal nutritional scores were associated with increased PAPP-A concentrations, lower UtA mean PI, and decreased placental volumes at the first trimester screening ultrasound, whereas no associations were detected with free β-HCG. The obtained measurements of placental volume were comparable with previous data and small variations could be firstly dependent on the mean gestational age at the ultrasound scan, as the placenta more than doubles its volume starting from 11 to 14 weeks [ 14 , 15 ]. The analysis on birth outcomes additionally showed a positive association between the maternal nutritional score and gestational age at birth ( p = 0.05).…”
Section: Discussionsupporting
confidence: 83%
“…55,56 A recent systematic review of 5 studies (302/5411 pregnancies with a subsequent diagnosis of SGA) using 3-dimensional placental volume to predict SGA birth showed inadequate screening test characteristics (sensitivity 25%, specificity 90%). 57 The method has similar performance characteristics to second-trimester UtAD to screen for FGR. 58…”
Section: Placental Infarctionmentioning
confidence: 89%
“…Previous studies have examined the association of first trimester PV with placental‐related pregnancy complications and have presented rather conflicting results . Plasencia et al found that PV is smaller in FGR pregnancies even after adjustment for maternal weight and fetal crown‐rump length (CRL).…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies have examined the association of first trimester PV with placental-related pregnancy complications and have presented rather conflicting results. [4][5][6][7][8][9][10][11] Plasencia et al 5 found that PV is smaller in FGR pregnancies even after adjustment for maternal weight and fetal crown-rump length (CRL). In line with these results, two other studies confirmed an association between PV measurement at 11 to 14 gestational weeks and birth weight (BW).…”
Section: Introductionmentioning
confidence: 99%